Decentralization, Regionalization and Adaptation (DRA) : Jamais deux sans trois - Advisory Board on English Education (2006)
The issue of regionalization—not just in education but also across the entire spectrum of government policy making and service delivery—is not a new one. In recent years two successive governments have made discussion of regionalization and decentralization a priority with a view to making government policies and services more responsive to local and regional needs.